Obesity‐related health impacts of active transport policies in Australia - a policy review and health impact modelling study - Vicki Brown; Marj Moodie; Linda Cobiac; Herrera Mantilla; Robert Carter (Elsevier, 2017)
Abstract Objective: To review Australian policies on active transport, defined as walking and cycling for utilitarian purposes. To estimate the potential health impact of achieving four active transport policy scenarios. Methods: A policy review was undertaken, using key words to search government websites. Potential health benefits were quantified using a cohort simulation Markov model to estimate obesity and transport injury‐related health effects of an increase in active transport. Health adjusted life years (HALYs) gained and healthcare cost savings from diseases averted were estimated. Budget thresholds to achieve cost‐effectiveness were estimated for each scenario. Results: There is broad recognition of the health‐related benefits of active transport from all levels of Australian government. Modelling results suggest significant health‐related benefits of achieving increased prevalence of active transport. Total HALYs saved assuming a one‐year effect ranged from 565 (95%UI 173-985) to 12,105 (95%UI 4,970-19,707), with total healthcare costs averted ranging from $6.6M (95%UI $1.9M‐11.3M) to $141.2M (95%UI $53.8M-227.8M). Conclusion: Effective interventions that improve rates of active transport may result in substantial healthcare‐related cost savings through a decrease in conditions related to obesity. Implications for public health: Significant potential exists for effective and cost‐effective interventions that result in more walking and cycling.